Cholangitis Lenta: A Clinicopathologic Study of 28 Cases. (December 2017) - Torous, Vanda F.; De La Cruz, A. Laura; Naini, Bita V.; Wang, Hanlin L.
Abstract : Cholangitis lenta, also known as ductular cholestasis, cholangiolar cholestasis, or subacute nonsuppurative cholangitis, is an uncommon type of cholangitis characterized by ductular reaction with inspissated bile in dilated ductules. The literature on this unique entity has been limited to only a few studies based on a very limited number of cases, which importantly suggest an association with sepsis and/or intra-abdominal infection. The clinical, laboratory, and histologic features of 28 cases of cholangitis lenta are herein investigated. Twenty-five (89.3%) patients were liver transplant recipients. Most notably, the majority of patients showed clinical signs and symptoms of sepsis, and positive microbiology cultures were demonstrated in 24 (85.7%) patients. Significantly, 15 (53.6%) patients died during their hospitalization, ranging from 2 days to 5 months after the initial liver biopsy that showed histologic features of cholangitis lenta. Among the 13 discharged patients, including 2 who received retransplantation, 4 (14.3%) subsequently died of pneumonia, graft dysfunction, or fungal infection within 7 months to 9.3 years. Only 9 (32.1%) patients were alive at the last follow-up, with the follow-up time ranging from 3.8 to 10.4 years. Our data show that the finding of cholangitis lenta on liver biopsy is thus frequently associated with sepsis and with a high mortality rate. Therefore, accurate diagnosis of this condition on liver biopsy is imperative as it is an indication that the patient may have a potentially life threatening condition that requires immediate medical attention and management.